Myocardial work indexes in elite athletes: An emerging echocardiographic tool to confirm physiologic cardiac remodeling in elite athletes with mildly reduced systolic function - Di Gioia, G.; Ferrera, A.; Mestrini, V.; Monosilio, S.; Mango, F.; Ortolina, D.; Pelliccia, A.; Squeo, M. R. (American Heart Journal, 2025)
Background Athlete's heart, characterized by cardiac chambers adaptations to exercise has some diagnostic overlaps with dilated cardiomyopathy (DCM). In the setting of differential diagnosis, myocardial work indexes (MWI), afterload-independent tool, could be helpful to identify early subclinical alterations. The aim of our study was to assess the utility of MWI in athletes with mildly reduced left ventricular ejection fraction (LVEF).